INCLUSIVE EDUCATION MANAGEMENT STRATEGY IN ISLAMIC BOARDING SCHOOL: A COLLABORATIVE APPROACH IN ACCOMMODING DIVERSITY - Fitriya, Firda Fina; Wahid, Abd Hamid; abdullah, abdullah (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research examines inclusive education management strategies in Islamic boarding schools, with a special focus on contextual, collaborative approaches in creating diversity-friendly education. This research aims to develop a unique collaboration model in the Islamic boarding school environment, combining the roles of Islamic boarding school leaders (kyai), teachers, students, families and communities in supporting the implementation of inclusive education. This research focuses on the Sabilillah Islamic Boarding School as a case study, with the aim of exploring how Islamic values and Islamic boarding school culture can be applied to accommodate the needs of various students, including those with special needs. The collaborative approach implemented at the Sabilillah Islamic Boarding School involves synergy between various parties, including Islamic boarding school leaders who build an inclusive vision based on Islamic teachings, teachers who develop adaptive curricula and group-based learning methods, as well as active involvement of families and communities in supporting the learning process. The inclusive education model developed does not only focus on academic aspects, but also on developing the character and social skills of students, while maintaining the distinctive religious and cultural values of Islamic boarding schools. The research results show that the implementation of inclusive education management strategies at the Sabilillah Islamic Boarding School has succeeded in integrating the principles of inclusivity with Islamic values, creating an educational environment that is fair, empathetic and respectful of differences. This research provides new insight into the importance of a contextual collaborative approach and the relevance of implementing Islamic boarding school cultural values in creating sustainable inclusive education. This discovery can be a model for other Islamic boarding schools in developing inclusive, fair and friendly education for all students. Keywords: Inclusive Education, Collaborative Approach, Educational Management, Islamic Boarding Schools, Islamic Values.